PRE-SERVICE TEACHERS’ ANXIETY DURING TEACHING PRACTICUM - Vina Agustiana (English Review: Journal of English Education, 2014)
Abstract: Teaching practicum is an obligatory task for students of Faculty of Teacher Training and Education to fulfill  their graduation requirement. Based on pre survey, this study aimed to find out the level of foreign language teaching anxiety (FLTA) experienced by English students and teachers throughout the teaching practicum. By using qualitative methods, 50 pre-service teachers completing their teaching practicum as part of their graduation requirement at English Department, Faculty of Teaching, participated in the study. The research tools were close-ended questionnaires filled by pre-service teachers and semistructured interviews conducted with 5 of the participant pre-service teachers. The analysis of the data revealed eight main categories as the foreign language student teacher anxiety: when the cooperative teacher and/or supervisor observe their teaching activity (3.6 mean rate), lack of teaching experience (3,4 mean rate), got stressed when they face the first day of teaching practicum (3,4 mean rate), conducting practicum assessment (3,1 mean rate), having a big class (2,9 mean rate), teaching grammar (2,8%), feeling worry if their students ask them questions (2,7 mean rate), and catching up students’ attention (2,6 mean rate). Lack of teaching experience and less of mastering the material caused the anxiety during teaching appeared. Therefore, before conduct teaching activity, it is a must to the techer to comprehend the material in order to avoid to make mistake and support our confident during teaching activity.Keywords: foreign language teaching anxiety, pre-service teachers, teaching practicum